Meningkatkan Hasil Belajar Bahasa Indonesia pada Materi Menyimak Teks Fiksi Menggunakan Model Pembelajaran Problem Based Learning di Sekolah Dasar - Benny Permana Putra; Arin Arianti; Agus Alim (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
The low learning outcomes Indonesian in listening to students' fictional texts are caused by the ineffective learning model used to make students less interested in following learning. The purpose of this study is to improve Indonesian learning outcomes by listening to fictional texts of grade 4 students of SD Negeri Jetis 01 Sukoharjo. This study included a type of classroom action research that was carried out in as many as two cycles. The subjects of this study were 30 grade 4 students. Data collection techniques in this study by providing tests and observations. Technical tests are used to see the learning outcomes of students and observation to see the success of problem-based learning models used in listening skills to fiction texts. Technical data analysts use quantitative and qualilative analysis techniques. The results of the study in cycle 1 showed an average value of 77.76, while in cycle II the average was 85.39. Observation of students' listening skills during the learning process using the problem-based learning model is in a good category so the problem-based learning model is very effective in Indonesian learning, listening material to fictional texts.